Show and Tell (S&T) Method in Students’ Speaking Skill - Nurmadina, Ice; Aderlaepe, Aderlaepe; Nurnia, Nurnia (Universitas Halu Oleo, 2021)
This study aims at investigating the effect of show and tell method on students’ speaking skill at the first grade of SMA Negeri 1 Bone Muna. The researcher applied a quasi-experimental design to find out whether there was a significant effect of show and tell method on students speaking skill. The population of this research was the first grade with the total of the students were 46 students. The sample taken by using cluster random sampling and the total sample was 23 students in the experimental class and 23 students in the control class. The researcher collected the data by giving pre-test in two classes, giving treatment in the experimental class by using show and tell method and conventional method in control class, and giving post-test in two classes to know students’ speaking skill after taught by show and tell method compared with the result in control class that taught by conventional method. The instrument of this research was an oral test. The data were analysed by using descriptive statistics and an inferential statistic that is counting in SPSS 16.0. To examine the hypothesis the researcher used an independent sample t-test. The result shows that students’ mean score of post-test in experimental class is raising. The factor that makes this study is raising because of the media used when students speak namely personal object or students' favourite object so students’ can express and develop their ideas based on these objects. Besides, show and tell method requires students to speak in front of the class so that students have the opportunity to practice their speaking. Therefore, show and tell method has a significant effect on students’ speaking skill at the first grade of SMA Negeri 1 Bone.